2019
DOI: 10.1080/13683500.2019.1637828
|View full text |Cite
|
Sign up to set email alerts
|

The ideal companion: the role of mobile phone attachment in travel purchase intention

Abstract: The ideal companion: the role of mobile phone attachment in travel purchase intention Recto running head : CURRENT ISSUES IN TOURISM Verso running head : P. RODRÍGUEZ-TORRICO ET AL.  2 A foundational understanding of attachment is based on attachment theory (Bowlby,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 67 publications
1
24
0
Order By: Relevance
“…This study's conceptual model is based on the stimulus‐organism‐response (SOR) model proposed by Mehrabian and Russell (1974). The SOR model is widely employed in tourism and agriculture (Jani & Han, 2014; Kim et al, 2018; Lee & Yun, 2015; Rajaguru, 2013; Rodríguez‐Torrico et al, 2019; Su & Swanson, 2017) to explain that an environmental stimulus (S) elicits a conscious and emotional reaction from a consumer (O), and this emotional reaction triggers the corresponding behavioral response (R) (Björk et al, 2010; Kani et al, 2017; Manthiou et al, 2016).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…This study's conceptual model is based on the stimulus‐organism‐response (SOR) model proposed by Mehrabian and Russell (1974). The SOR model is widely employed in tourism and agriculture (Jani & Han, 2014; Kim et al, 2018; Lee & Yun, 2015; Rajaguru, 2013; Rodríguez‐Torrico et al, 2019; Su & Swanson, 2017) to explain that an environmental stimulus (S) elicits a conscious and emotional reaction from a consumer (O), and this emotional reaction triggers the corresponding behavioral response (R) (Björk et al, 2010; Kani et al, 2017; Manthiou et al, 2016).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Concerning the response factors, in previous studies, purchase intention (Rodríguez-Torrico et al, 2019;Wu et al, 2013), behavioral intention (Flavi an et al, 2019), and revisit intention (Jani & Han, 2014) have been employed. In this study, online organic agricultural product purchase intention and rural health tourism intention are attributed as the response factors.…”
Section: Stimulus-organism-response Modelmentioning
confidence: 99%
“…It is suggested that, attachment is a crucial predictor of consumer behavioural intention (Yen et al, 2018;Yi et al, 2018). Previous studies have considered attachment as a direct precursor of consumer behavioural intention (Hosany et al, 2016;Kil et al, 2012;Rodríguez-Torrico et al, 2019). Additionally, attachment to Airbnb is a crucial factor that may influence consumers' behavioural intentions (Badrinarayanan and Becerra, 2019).…”
Section: Attachment To Airbnb and Guest Booking Intentionmentioning
confidence: 99%
“…Most of these characteristics relate to the findings and trends identified in the previous subsections and have a particularly strong impact on the implementation of tourism promotion. Tourism is becoming a highly personalized activity; therefore, tourist organizations have an excellent opportunity to use big data to learn about travel habits and needs of potential guests, and then offer customized services with an appropriate online shopping experience; mobility does not positively influence purchase intentions per se (Chuang, 2019), but only if the content is useful and adjusted to the context (Rodríguez-Torrico et al, 2019). Such targeting and personalization are becoming important digital priorities, which, of course, require web page adjustments.…”
Section: Evaluations Of Mobile Websites In the Tourismmentioning
confidence: 99%
“…Mobile apps in tourism have attracted quite a lot of interest in the research community, see, e.g. (Douglas, Lubbe, & van Rooyen, 2018;Gibbs, Gretzel, & Saltzman, 2016;Kamboj & Gupta, 2020;Ribeiro, Silva, Barbosa, Silva, & Metrôlho, 2018;Rodríguez-Torrico, Prodanova, San-Martín, & Jimenez, 2019;Tarantino, De Falco, & Scafuri, 2019). Unfortunately, not so much research was done on mobile web pages.…”
Section: Introductionmentioning
confidence: 99%